Stimuli-Responsive Hydrogels Based on Polyglycerol Crosslinked with Citric and Fatty Acids - Leidy C. Solano-Delgado; César A. Bravo-Sanabria; Carolina Ardila-Suárez; Gustavo E. Ramírez-Caballero (International Journal of Polymer Science)
Polyglycerol-based hydrogels from biodegradable raw materials were synthesized by crosslinking reactions of polyglycerol with citric and fatty acids. Three hydrogels were studied varying molar ratios of crosslinking agent. It was found that crosslink amount, type, and size play a crucial role in swelling, thermal, mechanical, and stimuli-responsive properties. The hydrogels absorption capacity changed in response to temperature and pH external stimuli. The hydrogel with the highest swelling capacity absorbed more than 7 times its own weight at room temperature and pH 5. This material increased 14 times its own weight at pH 10. Creep-recovery tests were performed to study the effect of crosslinking agent on mechanical properties. Deformation and percentage of recovery of synthesized hydrogels were obtained. Formation of hydrogels was confirmed using FTIR, and physicochemical properties were analyzed by Scanning Electron Microscopy (SEM), Differential Scanning Calorimetric (DSC), and Dynamic Mechanical Analysis (DMA). This paper aims to give a contribution to biobased hydrogel knowledge from chemical, physicochemical, and mechanical point of view.